Fc-dependent depletion of tumor-infiltrating regulatory T cells co-defines the efficacy of anti-CTLA-4 therapy against melanoma - Simpson, Tyler R; Li, Fubin; Montalvo-Ortiz, Welby; Sepulveda, Manuel A; Bergerhoff, Katharina; Arce, Frederick; Roddie, Claire; Henry, Jake Y; Yagita, Hideo; Wolchok, Jedd D; Peggs, Karl S; Ravetch, Jeffrey V; et al. (The Journal of experimental medicine, 2013)
Treatment with monoclonal antibody specific for cytotoxic T lymphocyte-associated antigen 4 (CTLA-4), an inhibitory receptor expressed by T lymphocytes, has emerged as an effective therapy for the treatment of metastatic melanoma. Although subject to debate, current models favor a mechanism of activity involving blockade of the inhibitory activity of CTLA-4 on both effector (T eff) and regulatory (T reg) T cells, resulting in enhanced antitumor effector T cell activity capable of inducing tumor regression. We demonstrate, however, that the activity of anti-CTLA-4 antibody on the T reg cell compartment is mediated via selective depletion of T reg cells within tumor lesions. Importantly, T reg cell depletion is dependent on the presence of Fcγ receptor-expressing macrophages within the tumor microenvironment, indicating that T reg cells are depleted in trans in a context-dependent manner. Our results reveal further mechanistic insight into the activity of anti-CTLA-4-based cancer immunotherapy, and illustrate the importance of specific features of the local tumor environment on the final outcome of antibody-based immunomodulatory therapies.